Metabolic effects of Cosmos caudatus Kunth (ulam raja) supplementation in type-2 diabetes mellitus patients - Cheng, Shi Hui (2017)
Cosmos caudatus, or locally known as “Ulam Raja” is a medicinal plant in Southeast Asia countries with reported medicinal benefits. Previously, supplementation with C. caudatus extract was found able to reduce plasma blood glucose in rats, but its effect in patients with type 2 diabetes mellitus (T2DM) was not established. To address this research gap, the present study aimed to determine the metabolic effects of C. caudatusin T2DM patients. The study was started by identifying the best way of C. caudatus supplementations. The first aim was to determine the antioxidant capacity of C. caudatusleaf extracts and juice using different extraction solvents (100% methanol, 100% ethanol, 95% ethanol, 50% ethanol). The findings found that C. caudatus leaves extracts had higher antioxidant capacity than C. caudatus juice . Following the first study, a two-arm randomized controlled clinical trial was carried out to determine the effectiveness and safety of C. caudatus supplementation in T2DM patients. A total of 101 T2DM patients (age: 49.7 ± 9.1 years; mean HbA1C: 8.8 ± 1.6 %; BMI: 29.8 ± 4.7 kg/m2; 56% male) were enrolled into the study. Participants were randomly assigned to diabetic-ulam group or diabetic controls. Patients in diabetic-ulam group consumed 15g of raw C. caudatus daily for 8 weeks while diabetic controls were abstained from taking C. caudatus. Both groups received standard lifestyle interventions. Changes in glycemic control, cardiovascular risk factors (anthropometric, blood pressure, lipid profile, high sensitivity C-reactive protein), renal profile, and liver function were measured at baseline, week 4, week 8 and week 12 (post-intervention follow-up) of the study. As compared to diabetic controls, C. caudatus consumption significantly reduced serum insulin (−1.16 versus +3.91 μU/ml in controls), lowered homeostasis model assessment of insulin resistance (HOMA-IR) (−1.09 versus +1.34 unit in controls), and increased quantitative insulin sensitivity check index (QUICKI) (+0.05 versus −0.03 unit in controls) in diabetic-ulam group. Subjects in diabetic-ulam group showed greater improvement in HbA1C (−0.76 %) as compared to diabetic controls (−0.37 %). Furthermore, supplementation of C. caudatus also resulted in the reduction of inflammation marker (hs-CRP) and systolic blood pressure, indicated its beneficial effect on reducing cardiovascular risk factors. Furthermore, C. caudatus consumption was found to be safe throughout the duration of the study as evident by no significant difference in liver and renal profile at the end of the study. Other parameters did not change significantly between the two groups. In addition, a proton nuclear magnetic resonance spectroscopy (1H NMR) based metabolomics approach was performed to determine the metabolic perturbation following C. caudatus consumption in T2DM patients. A total of 39 healthy individuals (age: 38.7 ± 8.5 years; BMI: 22.0 ± 1.7 kg/m2; 44% male) were recruited as healthy controls, and their urine and blood serum metabolic profiles were compared with those obtained from diabetic controls and diabetic-ulam groups. As compared to healthy individuals, the concentrations of urinary lactate, branched-chain amino acids (BCAA, including valine, leucine and isoleucine), alanine, lysine, glutamate, glutamine, and pyruvate were significantly increased in T2DM patients, whereas the concentration of urinary urea was significantly decreased in T2DM patients. In addition, concentrations of blood serum lactate, BCAA (valine, leucine and isoleucine), alanine, lysine, glutamate, and N-acetylglutamate were significantly elevated in T2DM patients as compared to healthy individuals. These findings are consistent with published literature. Following supplementation with C. caudatus, serum concentration of alanine, lactate and N-acetylglutamate were significantly decreased in diabetic-ulam group. The findings indicated a partial reversal of diabetes-induced metabolic changes through altered glycolysis, gluconeogenesis and glutamate metabolism. In addition, supplementation with C. caudatus was found to increase the concentration of urinary hippurate in diabetic-ulam group as compared to diabetic controls, suggesting changes in gut microflora metabolism. In conclusion, the current study provided evidence that supplementation with C. caudatus improved insulin sensitivity in T2DM patients, evidenced by improved HOMA-IR and QUICKI parameters. It also improved hs-CRP and systolic blood pressure in T2DM patients, suggesting its effect in reducing the cardiovascular risk factors. The current results also showed that C. caudatus did not negatively affect liver and renal functions, suggesting that it is safe for T2DM patients. Furthermore, metabolomic data showed that C. caudatus supplementation partially reversed some known diabetes-induced metabolic changes such as lactate and BCAA in blood and urine. In summary, the current study uncovered the beneficial potential of C. caudatusfor T2DM patients, and a longer term randomized controlled clinical trial is warranted to fully explore its therapeutic potential.